2016
DOI: 10.1038/ncomms10521
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial Dicer promotes atherosclerosis and vascular inflammation by miRNA-103-mediated suppression of KLF4

Abstract: MicroRNAs regulate the maladaptation of endothelial cells (ECs) to naturally occurring disturbed blood flow at arterial bifurcations resulting in arterial inflammation and atherosclerosis in response to hyperlipidemic stress. Here, we show that reduced endothelial expression of the RNAse Dicer, which generates almost all mature miRNAs, decreases monocyte adhesion, endothelial C–X–C motif chemokine 1 (CXCL1) expression, atherosclerosis and the lesional macrophage content in apolipoprotein E knockout mice (Apoe−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 68 publications
2
81
0
Order By: Relevance
“…miRCURY LNA TSBs were designed by Exiqon [39][40][41] . TSB-T3 selectively binds to a sequence overlapping the MRE-16 no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…miRCURY LNA TSBs were designed by Exiqon [39][40][41] . TSB-T3 selectively binds to a sequence overlapping the MRE-16 no.…”
Section: Methodsmentioning
confidence: 99%
“…Having demonstrated that TYRP1 mRNA dampens miR-16 activity, we challenged this sequestration model with small antisense oligonucleotides, known as target site blockers (TSBs) [39][40][41] . We designed two TSBs of 16 nucleotides in length: a control TSB (TSB-C1) that does not match any annotated human 3 UTR and a functional TSB (TSB-T3) that selectively binds to the sequence overlapping the TYRP1 MRE-16 site (2392-2407).…”
Section: Restoring Mir-16 Tumour Suppressor Function Reduces Tumour Gmentioning
confidence: 99%
“…Previous studies have demonstrated that endothelial miRNAs control endothelial functions and are implicated in the onset and development of cardiovascular disease 9,[19][20][21][22] . However, the role of endothelial miRNAs in BP homeostasis has been poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, the remaining Dicer1 allele might compensate for the phenotype of hemodynamics in EC-specific Dicer heterozygous KO mice. It has been reported that miRNAs are important regulators in cardiovascular diseases such as atherosclerosis and abdominal aortic aneurysms and potential therapeutic candidates regarding these diseases 9,20) . Therefore, further studies are needed to investigate the role of endothelial miRNA-mediated post-transcriptional gene regulation in the maintenance of BP homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation